(untitled) (Pain medicine, 2017)
Metamizole and acetaminophen are analgesics commonly used for pain relief in postoperative period in children and adults not only in Ukraine but also worldwide. This article highlights the experience of using these drugs in different countries depending on the duration of use, dose, sex, mechanisms of action and possible side effects. This document also discusses safety aspects of metamizol and acetaminophen comparing them with each other and with other drugs used for similar іndications. The risk of serious side effects of paracetamol is very low and dose-dependent. On account of metamizol, the most anticipated side effect is agranulocytosis, and its appearance depends on the duration of the drug use.